Morphological Assessment of Iron Oxide Nanoparticles Effects on the Chicken Embryo; Teratogenic Aspect - Ghasem Akbari; Mehdi Basaki; Marziyeh Hejazi; Heresh Rezaei; Mohammd Babaei (Negah Institute for Scientific Communication, 2022)
Introduction: In the last decades, magnetic nanoparticles have been considered and are being studied for employment in tumor therapy and imaging. Also, alongside their utilization in the role of MRI contrast factors, investigations of targeting tumor cells with biomolecules like anticancer drugs, antibodies, and siRNA, the utility of magnetic nanoparticles is evaluated. This preliminary work aimed to investigate the effects of iron oxide NPs on embryo growth and development with an emphasis on brain morphology and teratogenic effects.  Methods: After recognizing the air sac with candling, one hundred sixty fertile eggs of the Ross 308 broiler strains were divided into 8 groups (n=20). Group 1 (control) received 0.3 mL serum normal. Groups 2, 3, and 4 received iron oxide nanoparticles as maghemite with doses of 100, 250, and 500 ppm, respectively. Groups 5, 6, 7, and 8 received iron oxide NPs as magnetite with doses of 100, 250, 500, and 2500 ppm, respectively. Twenty days after injections, death day, chicken, brain, liver, heart, bursa of Fabricius, and spleen weights and teratogenic samples were recorded, and brain tissues from all chickens were collected for histological evaluations.  Results: The results demonstrated that iron oxide NPs had teratogenic effects such as the lack of formation of abdominal wall muscles and exposing the heart out of the thorax. Also, alterations were observed in the weight ratio of the liver, spleen, and bursa of Fabricius in experimental groups compared to the control group. In the microscopic assessment of the brain tissue, hyperemia, neuronophagia, edema around vessels, necrosis, and vacuolation of neurons were noticeable.  Conclusion: It can be concluded that iron oxide NPs affect the growth and development of embryos and can cross the BBB and penetrate the brain tissue by affecting brain morphology.